A Pallete of glass the America windows of Marc Chagall / produced, directed, written by Chuck Olin ; produced for the Art Institute of Chicago. - Olin, Chuck ([S.l.] Master Vision, 1977)
Documents the creation of Marc Chagall's American windows, located in the Chagall Gallery of Chicago's Art Institute. Shows how appropriate glass is chosen and blown into colored sheets and how Chagall applies the grisaile, the painted decorations that give unity and dimension to the glass fragments.
Title on cassette : Degas, Erte, Chagall.
Keywords: Chagall, Marc. American windows; Chagall, Marc; Chicago Art Institute; Glass painting and staining -- History. -- Illinois -- Chicago